Foundations in Autism Spectrum Disorders and Related Neurodevelopmental Disorders: Possible Causes, Characteristics, Diagnosis, and Treatment. - Greening, Neville K. (Advances in Social Sciences Research Journal, 2020)
Autism Spectrum Disorders (ASD) is a long life formative dysfunction characterized by symptomatic criteria that begins early in infants and continues throughout life. ASD is a condition that influences a child's sensory system that includes touch, smell, taste, hearing, and visual abilities. Typical forms of ASD in the pre-2013 DSM-5 manual also include Asperger's Syndrome; and Pervasive Developmental Disorder. The characteristics of these disorders are similar but may differ significantly. Children with ASD show difficulties or delays with social communication and necessary daily activities. Still, on the other hand, some may present themselves with the average ability to communicate both verbally and non-verbally. These disorders affect social interaction, behavior, interests, and other norms in life. Understanding the method of early intervention may include therapy and mediation that will assist in connecting natural and pharmacological approaches to deal with the treatment of ASD and distinguish standard or fundamental dynamic elements for advancing positive outcomes.